Primary endometrial squamous cell carcinoma with synchronous early stage Fallopian adenocarcinoma: A case report and review of diagnostic and treatment considerations - Margaret Caulkins; Jason Ricciuti; Rebeccah Stevens; Mohamed Desouki; Shashikant Lele (Elsevier, 2022)
Background: Primary endometrial squamous cell carcinoma (PESCC) remains a rare sub-type of endometrial cancer. This case is especially unique due to the incidental finding of early stage Fallopian adenocarcinoma. This report adds to the literature of this rare condition and discuss it's etiology, clinical course, and treatment regimen.Case: 65 year old postmenopausal female presented with postmenopausal bleeding. Dilation and curettage revealed endometrial highly atypical squamous epithelial proliferation. Staging procedure showed FIGO stage IB squamous cell carcinoma of the endometrium, without evidence of cervical involvement. A small focus of incidental poorly differentiated FIGO stage IA adenocarcinoma of the left Fallopian tube was discovered. She underwent six cycles of Paclitaxel and Cisplatin, and has remained disease free for two years. Conclusion: Primary endometrial squamous cell carcinoma is poorly understood entity. Early diagnosis is critical due to the strong correlation between initial stage and survival. Biopsy of the cervix and endometrium should be considered in cases of abnormal uterine sampling. The case presented is a prototypical example of PESCC, both in presentation, pathology, and course. It is especially unique due to synchronous high grade Fallopian adenocarcinoma.